Globalizacja a system zarządzania małym przedsiębiorstwem rodzinnym - Marjański, Andrzej (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
Globalization processes taking place in the business environment significantly influence the management of small family-run companies. Those companies, regardless of the industry, make an effort to prevent globalization from hampering their development and achieving success. They attempt to use the family image of their company to their advantage as a way of distinguishing themselves from other economic subject in the globalization world. The specificity of small family-run company management lies in combining limited means with family company characteristics. Small family-run companies in their attempt to reach success should use systems of management which take into account both the dangers and the opportunities created by the common market. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1184, s. 229-234